2012
DOI: 10.1136/bcr-02-2012-5855
|View full text |Cite
|
Sign up to set email alerts
|

FatalEnterococcus duransaortic valve endocarditis: a case report and review of the literature

Abstract: SummaryMost enterococcal endocarditis is caused by Enterococcus faecalis and Enterococcus faecium. Enterococcus durans is a rare member of non-faecalis, non-faecium enterococcal species and is found in the intestines of animals. E durans endocarditis is a very rare infection-only two cases of endocarditis in humans have been reported in the literature-and usually associated with good outcomes when treated with appropriate antibiotics. We report the first case of fatal E durans endocarditis. This patient had en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Elderly and immunocompromised patients are more susceptible to Enterococcal infection [6]. Similarly, reports of E. durans infection are also found for immunocompromised patients with cirrhosis [6] or after renal transplantation [10], as well as complex infections preceded by some form of therapy [3,8]. In the present case, as well, the patient’s long-term history of hemodialysis is considered to have been a risk factor.…”
Section: Discussionmentioning
confidence: 55%
“…Elderly and immunocompromised patients are more susceptible to Enterococcal infection [6]. Similarly, reports of E. durans infection are also found for immunocompromised patients with cirrhosis [6] or after renal transplantation [10], as well as complex infections preceded by some form of therapy [3,8]. In the present case, as well, the patient’s long-term history of hemodialysis is considered to have been a risk factor.…”
Section: Discussionmentioning
confidence: 55%
“…Identification of lactic acid bacteria. The lactic acid bacteria, MA15, and MC1 isolates were closely related to Enterococcus durans with 99.91% similarity as indicated by molecular identification based on 16S rDNA sequence data ( [34]. E. durans is non-faecalis enterococci found in the intestines of animals [34].…”
Section: Resultsmentioning
confidence: 93%
“…Although the growth patterns of E coli in the PN infusates in our study were broadly consistent with those found in other studies (see below), this remains a possibility. E durans , which is potentially pathogenic to humans, 14 , 15 was an unexpected contaminant of the reference E coli used to inoculate the bags containing PN infusates. On the other hand, this contamination can be regarded as fortunate since it allowed this study to illustrate that 2 different microorganisms can behave qualitatively and quantitatively differently in the same PN‐related infusates at the same time under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci are frequently isolated from both hospitalized inpatients receiving PN 10 and ambulatory patients receiving long‐term PN 10 , 11 . The facultative anaerobe Enterococcus durans has only occasionally caused serious 14 and fatal 15 infection.…”
Section: Introductionmentioning
confidence: 99%